2014
DOI: 10.1002/jobm.201400317
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma species mediated differential tolerance against biotic stress of phytopathogens in Cicer arietinum L.

Abstract: Trichoderma spp. have been reported to aid in imparting biotic as well as abiotic tolerance to plants. However, there are only few reports unfolding the differential ability of separate species of Trichoderma genera generally exploited for their biocontrol potential in this framework. A study was undertaken to evaluate the biocontrol potential of different Trichoderma species namely T. harzianum, T. asperellum, T. koningiopsis, T. longibrachiatum, and T. aureoviride as identified in the group of indigenous iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 37 publications
1
15
0
2
Order By: Relevance
“…Additionally, the bio-control activities of T. harzianum against F. oxysporum f. sp. ciceri, R. solani modulate the induced plant resistance and enhance the plant growth (Sivan, 1989, Malik et al, 2005, Saxena et al, 2015. These results support the present findings of controlling soil-borne diseases as well as increasing growth promoting parameters and seed yield of chick pea by Trichoderma fortified composting.…”
Section: IVsupporting
confidence: 89%
“…Additionally, the bio-control activities of T. harzianum against F. oxysporum f. sp. ciceri, R. solani modulate the induced plant resistance and enhance the plant growth (Sivan, 1989, Malik et al, 2005, Saxena et al, 2015. These results support the present findings of controlling soil-borne diseases as well as increasing growth promoting parameters and seed yield of chick pea by Trichoderma fortified composting.…”
Section: IVsupporting
confidence: 89%
“…Of the two fungal species, T. harzianum has been well studied as biocontrol agent (BCA) for control of B. cinerea as well as many other plant pathogens (Harman et al, 2004;Verma et al, 2007;Vos et al, 2015), whereas T. koningiopsis has been rarely studied as BCA for plant diseases so far. This fungus has been recorded in many countries, including Brazil (Lopes et al, 2012;De Souza et al, 2016), China (Sun et al, 2012), Columiba (Moreno et al, 2009;Smith et al, 2013), France (Jaklitsch and Voglmayr, 2015), India (Saxena et al, 2015), Mexico (Mendoza et al, 2011) and Poland (Błaszczyk et al, 2011), implying that it might be a cosmopolitan soilborne fungus. Previous studies indicated that selected isolates of T. koningiopsis are effective biocontrol agents (BCAs) in suppression of plant pathogens, including Fusarium oxysporum f.sp.…”
Section: Discussionmentioning
confidence: 99%
“…These treatments also significantly increased early and total fresh pods yield. Similarly, Saxena et al (2015) reported enhancement in root and shoot lengths along with dry weight of plants with significant increase in the number of leaf in the plants treated with the Trichodemra isolate BHUF4.…”
Section: Vegetative Growth and Total Fresh Pods Yieldmentioning
confidence: 75%